2016
DOI: 10.1038/srep30743
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of hippocampal NMDA GluN2B receptors regulated by fear conditioning determines its contribution to memory consolidation in adult rats

Abstract: The number and subtype composition of N-methyl-d-aspartate receptor (NMDAR) at synapses determines their functional properties and role in learning and memory. Genetically increased or decreased amount of GluN2B affects hippocampus-dependent memory in the adult brain. But in some experimental conditions (e.g., memory elicited by a single conditioning trial (1 CS-US)), GluN2B is not a necessary factor, which indicates that the precise role of GluN2B in memory formation requires further exploration. Here, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Blockade of GluN2B activity in vivo in adult rodents following the induction of LTP can block its decay (Sachser et al, 2016) suggesting that GluN2B plays a critical role in updating memory traces. Indeed, GluN2B antagonism in the CA1 has been shown to impair hippocampal-dependent learning and memory tasks such as object recognition (Sachser et al, 2016) and contextual fear conditioning (Sun et al, 2016). Further supporting its role in plasticity, genetic overexpression of GluN2B in the CA1 enhances LTP in adult and aged mice, as well as adult rats (Cao et al, 2007; Tang et al, 1999; Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of GluN2B activity in vivo in adult rodents following the induction of LTP can block its decay (Sachser et al, 2016) suggesting that GluN2B plays a critical role in updating memory traces. Indeed, GluN2B antagonism in the CA1 has been shown to impair hippocampal-dependent learning and memory tasks such as object recognition (Sachser et al, 2016) and contextual fear conditioning (Sun et al, 2016). Further supporting its role in plasticity, genetic overexpression of GluN2B in the CA1 enhances LTP in adult and aged mice, as well as adult rats (Cao et al, 2007; Tang et al, 1999; Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in NMDAR subunits level have also been described following fear conditioning, Sun et al [ 49 ] have shown that there was a rapid and transient increase in the amount of membrane GluN2B-NMDARs (as both GluN1 and GluN2B increased) in CA1 area, 5 to 10 minutes after a single-trial fear conditioning training. The authors proposed that GluN1 and GluN2B increases depend on GluN2B activation, as it was blocked by GluN2B inhibitors.…”
Section: Nmdar Expression and Memory Acquisition ( Tablementioning
confidence: 99%
“…The authors proposed that GluN1 and GluN2B increases depend on GluN2B activation, as it was blocked by GluN2B inhibitors. Accordingly, Sun et al have also suggested that the reported subunit increase could depend on training strength, as a 5-trial conditioning induced higher subunits levels than a single-trial training [ 49 ].…”
Section: Nmdar Expression and Memory Acquisition ( Tablementioning
confidence: 99%
“…Trace fear conditions increase the spiking of projection neurons in the inferior-limbic prefrontal cortex (IL-PFC) and basolateral amygdala (BLA) [20]. NMDARs are required for learning and memory and their subunits undergo dynamic modification following fear conditioning [21][22][23][24]. Inhibition of NMDARs prevents the loss of brain-derived neurotrophic factor (BDNF) function [25].…”
Section: Introductionmentioning
confidence: 99%